2015
DOI: 10.1165/rcmb.2014-0168oc
|View full text |Cite
|
Sign up to set email alerts
|

Targeting of Plasminogen Activator Inhibitor 1 Improves Fibrinolytic Therapy for Tetracycline-Induced Pleural Injury in Rabbits

Abstract: Endogenous active plasminogen activator inhibitor 1 (PAI-1) was targeted in vivo with monoclonal antibodies (mAbs) that redirect its reaction with proteinases to the substrate branch. mAbs were used as an adjunct to prourokinase (single-chain [sc] urokinase [uPA]) intrapleural fibrinolytic therapy (IPFT) of tetracycline-induced pleural injury in rabbits. Outcomes of scuPA IPFT (0.25 or 0.0625 mg/kg) with 0.5 mg/kg of mouse IgG or mAbs (MA-33H1F7 and MA-8H9D4) were assessed at 24 hours. Pleural fluid (PF) was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

13
133
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(147 citation statements)
references
References 34 publications
13
133
0
Order By: Relevance
“…We also found that the intrapleural level of active PAI-1 dramatically affects the half-life of fibrinolysins and outcome of IPFT and that in vivo PAI-1 neutralization improves IPFT outcomes and decreases the required effective dose of a fibrinolysin (14). In the present study, we used chest ultrasonography (US) and computed tomography (CT) imaging modalities to define the time course for effective intrapleural fibrinolysis after IPFT by using known minimal effective doses (MED) of sc tissue PA (sctPA) and scuPA in our well-characterized TCN-induced pleural injury in rabbits (14,24,31,35). We found that the time needed for effective fibrinolysis for sctPA and scuPA were similar and protracted over several hours.…”
mentioning
confidence: 61%
See 4 more Smart Citations
“…We also found that the intrapleural level of active PAI-1 dramatically affects the half-life of fibrinolysins and outcome of IPFT and that in vivo PAI-1 neutralization improves IPFT outcomes and decreases the required effective dose of a fibrinolysin (14). In the present study, we used chest ultrasonography (US) and computed tomography (CT) imaging modalities to define the time course for effective intrapleural fibrinolysis after IPFT by using known minimal effective doses (MED) of sc tissue PA (sctPA) and scuPA in our well-characterized TCN-induced pleural injury in rabbits (14,24,31,35). We found that the time needed for effective fibrinolysis for sctPA and scuPA were similar and protracted over several hours.…”
mentioning
confidence: 61%
“…Female New Zealand white rabbits, weighing 3.0 -3.6 kg, were used (n ϭ 27). Pleural injury was induced by intrapleural administration of a single dose of TCN, as previously reported (14,24). Single intrapleural doses of either scuPA (Abbott Laboratories) or tPA (Activase, Genentech), known to clear pleural organization (MEDs 0.5 mg/kg and 0.145 mg/kg, respectively) in the model (in n ϭ 12 and 10 rabbits, respectively), or a vehicle control (n ϭ 3) were administered 48 h after induction of pleural injury by TCN (26).…”
Section: Methodsmentioning
confidence: 79%
See 3 more Smart Citations